Dentoskeletal changes and anteroposterior improvements in skeletal class III malocclusion treated with MEAW: A retrospective study - Phi Ngoc Quang Tran; Anh Hoang Cu; Minh Ngoc Thuy Tran; Vy Ngoc Thuy Tran (PLoS ONE, 2026)
Background Skeletal Class III malocclusion is a severe dentofacial deformity that often requires surgical correction, but the associated risks have increased interest in non-surgical alternatives. The multiloop edgewise archwire (MEAW) technique has been used as a conservative option. The aim of this study was to investigate the dentoskeletal changes associated with the MEAW technique in treating skeletal Class III malocclusion, with a particular focus on improvements in anteroposterior bimaxillary relationships and comparison with surgical outcomes. Methods This retrospective study included 60 patients with skeletal Class III malocclusion, comprising 30 treated with the MEAW technique and 30 matched patients who underwent orthognathic surgery. Dentoskeletal parameters were assessed on pre- and post-treatment lateral cephalograms. Pearson’s correlation analysis and multiple linear regression were performed to identify factors associated with improvements in anteroposterior relationships. Results Significant dental and skeletal changes were observed, including alterations in incisor inclination and bimaxillary measurements ( p < 0.05). Post-treatment, anteroposterior relationships improved significantly, with changes strongly associated with increases in the BaNA angle and decreases in the SNB angle. However, compared to the surgical group, the MEAW group demonstrated less pronounced improvements in anteroposterior bimaxillary relationships. Regression analysis identified the BaNA angle and incisor inclination as key contributors. Conclusions Although the effect is less pronounced than in the case of surgical intervention, the MEAW technique effectively improves anteroposterior bimaxillary relationships in skeletal Class III malocclusion. These findings suggest that MEAW is a valuable non-surgical alternative for selected skeletal Class III patients.